ANALISIS STILISTIKA NOVEL DAUN YANG JATUH TAK PERNAH MEMBENCI ANGIN KARYA TERE LIYE DAN NOVEL BELENGGU MERAH MUDA KARYA TYAS DAMARIA - Melo Kasmarani (Jurnal Pembahsi (Pembelajaran Bahasa Dan Sastra Indonesia), 2017)
This research is to determine the novel by using analytical descriptive method. The uniqueness of the language use in the novel “Sehelai Daun yang Jatuh Tak Pernah Membenci Angin” by Tere Liye and the novel  “Belenggu Merah Muda” by Tyas Damaria where the novel is motivated by socio-culture factors  and educational’s writer are express through story description. In the novel of Sehelai Daun yang Jatuh Tak pernah Membenci Angin” that has 41 usage of foreign language where included in phrases, clauses, or quotations. Besides, it has 11 usages of knowledge, whether it is social knowledge, medical science, law, and many others. There also 3 usages of greetings, meanwhile there are 7 language style in the sentences of metaphors, 1 metonymic, 15 similes, 10 idioms, 4 connotations, 6 personification, 54 hyperboles, 70 tautologies, and 1 figurative. In other novel “Belenggu Merah Muda” by Tyas Damaria, there are 37 usages of foreign language that consist of phrases, clauses or quotations. Where it has 15 usages of foreign language whether it is socio-culture, medical science, law, and many others, it also has language style such as 3 sentences in metaphors, 0 metonymic, 14 similes, 26 idioms, 1 connotations, 14 personifications, 10 hyperboles, 24 tautologies, and1 figurative. In this research, the writer concludes that in the Tere Liye’s novel and Tyas Damaria’s  novel are the novel that has the differences of unique and the language style that give statistical effect. Keywords: Stilistika, Novel “Sehelai Daun yang Jatuh Tak Pernah Membenci Angin, Novel Belenggu Merah Muda, Language Style